2019
DOI: 10.1111/1750-3841.14412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Fermentation Strains on the Flavor Characteristics of Fermented Soybean Curd

Abstract: The effects of different fermentation strains on the flavor characteristics of fermented soybean curd (FSC) were investigated in this study. Fresh tofu was fermented by Actinomucor elegans, Rhizopus arrhizus, Mucor racemosus, and Rhizopus chinensis, either alone or in various combinations. The FSC manufacturing process included prefermentation by different strains at 28 °C for 60 hr, followed by salting at 16 °C for 7 days and finally proceeding postfermentation at 25 °C for 35 days. Subsequently, five tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
5
10
0
Order By: Relevance
“…According to the PCA biplot, all samples were significantly differentiated: tofu was significantly different from furu, furu fermented with Mucor racemosus and Mucor wutungklao had a high similarity while they were different from Actinomucor . These results confirmed that strain led to different aroma profiles, and this was similar to the previous findings (Li et al., 2018; Liu et al., 2019; Zhuang et al., 2017). PCA showed the correlation between aroma compounds and samples: this separation was mainly due to a group of compounds including creosol, octanal, (E)‐2‐octenal, citral, benzaldehyde, 2‐dodecanone, carvone, 4‐methylvaleric acid, (2E)‐2‐undecenoic acid, 1‐hexanol, 1‐octen‐3‐ol, linalool, methyl salicylate, ethyl caprylate, ethyl hexadecanoate, ethyl phenylacetate, ethyl 3‐phenylpropionate, ethyl oleate, ethyl linoleate, isoamyl acetate, and 2‐pentylfuran (PC1, 77.9%).…”
Section: Resultssupporting
confidence: 92%
“…According to the PCA biplot, all samples were significantly differentiated: tofu was significantly different from furu, furu fermented with Mucor racemosus and Mucor wutungklao had a high similarity while they were different from Actinomucor . These results confirmed that strain led to different aroma profiles, and this was similar to the previous findings (Li et al., 2018; Liu et al., 2019; Zhuang et al., 2017). PCA showed the correlation between aroma compounds and samples: this separation was mainly due to a group of compounds including creosol, octanal, (E)‐2‐octenal, citral, benzaldehyde, 2‐dodecanone, carvone, 4‐methylvaleric acid, (2E)‐2‐undecenoic acid, 1‐hexanol, 1‐octen‐3‐ol, linalool, methyl salicylate, ethyl caprylate, ethyl hexadecanoate, ethyl phenylacetate, ethyl 3‐phenylpropionate, ethyl oleate, ethyl linoleate, isoamyl acetate, and 2‐pentylfuran (PC1, 77.9%).…”
Section: Resultssupporting
confidence: 92%
“…Mold‐fermented sufu is the most common type in various regions in China, and it is generally believed that mucor plays a decisive role in the fermentation of sufu . Baixi sufu seems to belong to this type because few instances of Mucor flavus were identified, and the mucor has been reported in sufu previously .…”
Section: Discussionmentioning
confidence: 59%
“…Geotrichum candidum therefore seems to be a potential explanation for BS fermentation with a short period and unique flavor, rather than mucor or other typical sufu starters. Interestingly, the fermentation pattern of BS is different from previous research . Although sufu has long been considered as a cheese‐like product, to the best of our knowledge, G. candidum was hardly found in sufu fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Phenol is not only an important flavor compound, but is also a bactericide. Phenol has also been produced by A. elegans during the fermentation of soybean curd …”
Section: Resultsmentioning
confidence: 99%
“…Phenol has also been produced by A. elegans during the fermentation of soybean curd. 19 Acids, amines, and nitriles, except for benzenepropanenitrile ( Fig. 3(B)), were all produced during fermentation.…”
Section: Changes In Volatiles In Raw Rsm and During Fermentationmentioning
confidence: 98%